An experiment on the Nash program: Comparing two strategic mechanisms implementing the Shapley value - Michela Chessa; Nobuyuki Hanaki; Aymeric Lardon; Takashi Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2022)
We experimentally compare two well-known mechanisms inducing the Shapley value as an ex ante equilibrium outcome of a noncooperative bargaining procedure: the demand-basedWinter's demand commitment bargaining mechanism and the offer-based Hart and Mas-Colell procedure. Our results suggest that the offerbased Hart and Mas-Colell mechanism better induces players to cooperate and to agree on an efficient outcome, whereas the demand-based Winter mechanism better implements allocations that reflect players' effective power.
Keywords: C70; C71; C92; 330; Nash program; Bargaining procedures; Shapley value; Experiments